2021
DOI: 10.3390/ijerph182312545
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Anti-SARS-CoV-2 Antibodies among Municipal Staff in the Municipality of Prishtina

Abstract: Background: Some studies have assessed the seroprevalence of anti-SARS-CoV-2 antibodies in different populations. Very few studies have explored seroprevalence in municipal workers, an important and potentially high-risk population. This study aims to determine the prevalence of anti-SARS-CoV-2 antibodies in municipal workers, with the additional examination of the association of prevalence with various demographic, health-related, and epidemiological factors. Methods: We surveyed and tested for seroprevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Another study by our group has examined the seroprevalence of anti-SARS-CoV-2 antibodies in municipal workers in Prishtina municipality. Out of 418 municpal workers surveyed, we found that 21.1% were seropositive for either IgG or IgM, of which 9.6% were positive for IgM and 19.4% for IgG [ 33 ]. There are some studies that previously have examined seroprevalence among HCWs in primary healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by our group has examined the seroprevalence of anti-SARS-CoV-2 antibodies in municipal workers in Prishtina municipality. Out of 418 municpal workers surveyed, we found that 21.1% were seropositive for either IgG or IgM, of which 9.6% were positive for IgM and 19.4% for IgG [ 33 ]. There are some studies that previously have examined seroprevalence among HCWs in primary healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…em servidores municipais semelhante a este estudo (15) . Resultado similar foi encontrado em oito instalações de serviços de administração pública em Genebra, Suíça (16) .…”
unclassified